ANALISIS PEMBAGIAN SISA HASIL USAHA BAGI ANGGOTA KOPERASI KARYAWAN HOTEL MARGA JAYA DI SAMARINDA, TAHUN 2007-2011 - Rahim, Abdul (EKONOMIA, 2012)
Â The purposes of this research is to analyze the division of Business Revenue Residu (BRR) of the Cooperative for Hotel Marga Jaya employee in Samarinda for year 2007-2011 which utilized the calculation techniques of Sitio and Tamba based on the members activities, which is from saving either from primary saving or obligatory saving, loan, and purchase of things.